Comparison of miniscrew-anchored maxillary protraction protocols: a randomized clinical trial - Miranda, Felicia (2020)
Introduction: The aim of this randomized clinical trial was to compare the dentoskeletal and airway outcomes of miniscrew-anchored maxillary protraction using hybrid and conventional hyrax expanders in growing Class III subjects. Methods: Forty patients were randomized into two groups. Group HH was composed by patients with Class III malocclusions treated with a hybrid hyrax expander with two miniscrews in the maxilla and two miniscrews in the anterior region of the mandible. Class III elastics were used from the maxillary first molar to the mandibular miniscrews until anterior crossbite correction or a maximum 12 months of treatment. The group CH was treated with a similar protocol except for the conventional Hyrax expander in the maxilla. Conebeam computed tomography exams and digital dental models were obtained before expansion (T1) and after treatment (T2). The primary outcomes included the sagittal skeletal effects produced with treatment. The secondary outcomes included the upper airway changes and transversal changes in the maxillary structures. Intergroup comparison was performed using t tests and Mann-Whitney U tests (p<0.05). Results: The final sample comprised 18 subjects (8 female, 10 male; initial age of 10.80 years) in Group HH and 14 subjects (6 female, 8 male; initial age of 11.44 years) in Group CH. A greater increase in maxillomandibular skeletal relationship and maxillary length was observed for the HH group. Both groups presented similar skeletal vertical and orthodontic outcomes after maxillary protraction. The oropharynx and the most constricted area of oropharynx increased similarly in both groups. Significantly greater increases in the nasal cavity width and buccal alveolar crest width were found for group HH. The maxillary interpremolar distance showed a greater increase in group CH. Conclusions: Miniscrew-anchored maxillary protraction using hybrid expanders produced greater orthopedic effects with better control of dental side effects and constitute an alternative for growing Class III malocclusion patients. No differences in upper airway changes were observed using maxillary protraction anchored on hybrid or conventional hyrax expanders.